Effects of student's satisfaction and co-creation on the relationship between attitudinal factors and destination loyalty: evidence from international students in Malaysian public universities
In view of the ever increasing attrition rate of international students at study destinations occasioned by increased education marketization, reduced public budgetary allocation, globalization, internationalization and stiff competition, this study aimed to fill research vacuum by proposing and validating destination loyalty model using new paradigm of relationship marketing in higher education sector. Drawing from a new marketing innovation concept of service dominant (SD) logic and social exchange theory, this study examines the effects of students’ satisfaction and Co-Creation on the relationship between attitudinal factors and destination loyalty. A total of 498 undergraduate and post graduate international students from Malaysian public universities participated in the survey. The result of partial least square (PLS) path analysis supported all but two variables in the hypothesized direct relationship to students’ satisfaction and destination loyalty. Specifically, attitudinal factors of service quality, perceived value and personal reasons were found to have significant relationship with destination loyalty. Similarly, service quality, perceived image and perceived value significantly influenced students’ satisfaction. The intervening variables of students’ satisfaction and Co-creation also show significant relationship with destination loyalty.However, perceived image was not significant to destination loyalty. Personal reason was also not significant with students’ satisfaction. The bootstrapping result of students’ satisfaction as mediator was significant except with personal reasons. The results of the analysis also suggest that Co-Creation moderates the relationship between students’ satisfaction and destination loyalty. Taken together, the findings of this study lend empirical support to the view that joint creation of value between consumers and service providers will confer competitive advantage in service relationship. Hence, knowledge of FP-4 in SD logic will assist universities management to grow their student’s profile for sustainable competitive advantage. It is recommended that emerging destinations should concerntrate on retention through unique service provision. Malaysian public universities particularly should focus on the implementation of students’ satisfaction and Co-Creation to earn students’ loyalty and increase inbound international students for sustainable internationalization benefits.